Gender, Productive Resources and Agricultural Development in the Urban Area ABSTRACT. - Olufemi, Damilola Blessing; Adejumo, Olusola Joseph (Journal of Gender and Power, 2021)
The Nigerian society is a patriarchy society where men dominate over women most especially in access and control over productive resources and decision-making process. This limitation often has negative impacts on food security; most especially in urban areas where more than half of the world’s population now dwells. This study aimed at documenting the experiences of urban women farmers in accessing critical agricultural productive resources. The study engaged both quantitative and qualitative methods in designing the research. Multistage sampling technique was used to select 250 respondents, and information was elicited through the use of questionnaire, Key Informant Interview (KII), and Focus Group Discussion (FGD). The study revealed that the urban female farmers in the study area have inadequate access to critical agricultural productive resources and are still making use of crude and traditional implements in their various agricultural activities. Likewise, through usufructuary rights, in reference to access to land the urban status quo is gradually weakening the patriarchal nature of the society.